Whipple Grossing in the Era of New Staging: Should We Standardize? - Jiaqi Shi (Diagnostics, 2019)
Whipple procedure, also known as pancreatoduodenectomy, is the most common surgery for the removal of tumors of the head of the pancreas, ampulla, distal common bile duct, or periampullary duodenum. It is also one of the most challenging resection specimens grossed by surgical pathologists. A thorough and consistent evaluation of the gross surgical specimen is the most critical first step for accurate diagnosis, determination of tumor origin, staging, and evaluation of margin status. However, there has been no standard grossing protocol for Whipple specimens, which has led to inaccurate diagnoses, staging, and inconsistent reporting. This issue has become even more challenging in the era of the size-based tumor staging systems recommended by the new 8th Edition of the American Joint Committee on Cancer (AJCC) Cancer Staging Manual. Moreover, new concerns have been raised regarding how to best evaluate margin status and lymph nodes. Studies have shown that different Whipple grossing methods can significantly impact margin assessment and lymph node yield and thus affect R0/R1 status and clinical stage. Other important issues under debate include nomenclature, definitions of margin (versus surface), and R1 status. Consistent Whipple grossing and standardization of reporting will provide better communication and more accurate diagnosis and staging, as well as prognostic prediction.